Sign Of Gender Equality And The Adolescents’ Identity In MOXIE! Movie Script - Chairunnisa , Chairunnisa L.; Moelier, Dahlia D.; Asyrafunnisa, Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2023)
This research aimed to find out the interpretations of the signs that appear in the movie script, and how women survive from gender discrimination in the MOXIE! movie script. The writer used qualitative descriptive, semiotics, and liberal feminism approach in analyzing the data. The data were obtained by reading and comprehending, collecting and classified, identified, and explaining the interpretations of the signs and how women survive from gender discrimination based on Peirce and Saussure theories. The result shows that there were three triadic types of signs used in MOXIE! movie script, they were (1) sign or representamen which consisted of qualisign and leg signs, (2) object which consisted of icon, index, and symbol, and (3) interpretant which consisted of decent sign or dicisign, and argument. There were also 4 types of signs included in gender equality there were marginalization, stereotypes, subordination, and violence. Then liberal feminism that stream accentuated putting women who had full and individual opportunities.